2012
DOI: 10.1111/j.1600-0757.2011.00400.x
|View full text |Cite
|
Sign up to set email alerts
|

Decreased bone mineral density and periodontal management

Abstract: The definition of osteoporosis has evolved beyond low bone mineral density to include impaired bone morphology and matrix properties. As such, the subsequent bone density insufficiencies extend beyond the skeletal risks of fracture and have implications for oral health management patients. As our population ages there is a worldwide increase in the risk of decreased bone mineral density and its subsequent morbidity. This makes age an independent risk factor for fracture and decreased bone mineral density. Mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 158 publications
(228 reference statements)
0
23
0
Order By: Relevance
“…Osteoporosis may be a predisposing factor for alveolar bone loss in periodontal disease and vice versa, periodontitis could be an earliest sign of osteoporosis. Decreased bone density in the active sites of periodontitis may result in favouring a consequent accelerated progression of the host inflammatory response to the parodontopathogens, the elevation of systemic levels of cytokine that further increases the loss of bone density and risk of tooth loss (46). Crosssectional studies showed evidence that mandibular bone mass was significantly correlated with skeletal bone mass (47)(48)(49)(50).…”
Section: Vitamin D and Periodontal Diseasementioning
confidence: 90%
“…Osteoporosis may be a predisposing factor for alveolar bone loss in periodontal disease and vice versa, periodontitis could be an earliest sign of osteoporosis. Decreased bone density in the active sites of periodontitis may result in favouring a consequent accelerated progression of the host inflammatory response to the parodontopathogens, the elevation of systemic levels of cytokine that further increases the loss of bone density and risk of tooth loss (46). Crosssectional studies showed evidence that mandibular bone mass was significantly correlated with skeletal bone mass (47)(48)(49)(50).…”
Section: Vitamin D and Periodontal Diseasementioning
confidence: 90%
“…Osteoporosis is considered a “modifiable risk factor” for periodontitis with regard to host modulation therapy [23•, 72••, 73]. Osteoporotic elderly women who were not treated for the condition have a higher risk for severe periodontal disease [74•].…”
Section: Interdisciplinary Management Of Osteoporosis and Periodontitismentioning
confidence: 99%
“…The decreased bone mass in periodontitis may result in sites with accelerated progression of bone loss, in the presence of oral biofilm infection and host immunological responses, due to the fragility of the bony housing of the teeth. Dense trabeculation was a strong indicator of high bone mineral density, and sparse trabeculation may be used to predict low bone mineral density (5).…”
Section: Introductionmentioning
confidence: 99%